(5x-2)(5x+2)=25x-7x

Simple and best practice solution for (5x-2)(5x+2)=25x-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x-2)(5x+2)=25x-7x equation:


Simplifying
(5x + -2)(5x + 2) = 25x + -7x

Reorder the terms:
(-2 + 5x)(5x + 2) = 25x + -7x

Reorder the terms:
(-2 + 5x)(2 + 5x) = 25x + -7x

Multiply (-2 + 5x) * (2 + 5x)
(-2(2 + 5x) + 5x * (2 + 5x)) = 25x + -7x
((2 * -2 + 5x * -2) + 5x * (2 + 5x)) = 25x + -7x
((-4 + -10x) + 5x * (2 + 5x)) = 25x + -7x
(-4 + -10x + (2 * 5x + 5x * 5x)) = 25x + -7x
(-4 + -10x + (10x + 25x2)) = 25x + -7x

Combine like terms: -10x + 10x = 0
(-4 + 0 + 25x2) = 25x + -7x
(-4 + 25x2) = 25x + -7x

Combine like terms: 25x + -7x = 18x
-4 + 25x2 = 18x

Solving
-4 + 25x2 = 18x

Solving for variable 'x'.

Reorder the terms:
-4 + -18x + 25x2 = 18x + -18x

Combine like terms: 18x + -18x = 0
-4 + -18x + 25x2 = 0

Begin completing the square.  Divide all terms by
25 the coefficient of the squared term: 

Divide each side by '25'.
-0.16 + -0.72x + x2 = 0

Move the constant term to the right:

Add '0.16' to each side of the equation.
-0.16 + -0.72x + 0.16 + x2 = 0 + 0.16

Reorder the terms:
-0.16 + 0.16 + -0.72x + x2 = 0 + 0.16

Combine like terms: -0.16 + 0.16 = 0.00
0.00 + -0.72x + x2 = 0 + 0.16
-0.72x + x2 = 0 + 0.16

Combine like terms: 0 + 0.16 = 0.16
-0.72x + x2 = 0.16

The x term is -0.72x.  Take half its coefficient (-0.36).
Square it (0.1296) and add it to both sides.

Add '0.1296' to each side of the equation.
-0.72x + 0.1296 + x2 = 0.16 + 0.1296

Reorder the terms:
0.1296 + -0.72x + x2 = 0.16 + 0.1296

Combine like terms: 0.16 + 0.1296 = 0.2896
0.1296 + -0.72x + x2 = 0.2896

Factor a perfect square on the left side:
(x + -0.36)(x + -0.36) = 0.2896

Calculate the square root of the right side: 0.538144962

Break this problem into two subproblems by setting 
(x + -0.36) equal to 0.538144962 and -0.538144962.

Subproblem 1

x + -0.36 = 0.538144962 Simplifying x + -0.36 = 0.538144962 Reorder the terms: -0.36 + x = 0.538144962 Solving -0.36 + x = 0.538144962 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.36' to each side of the equation. -0.36 + 0.36 + x = 0.538144962 + 0.36 Combine like terms: -0.36 + 0.36 = 0.00 0.00 + x = 0.538144962 + 0.36 x = 0.538144962 + 0.36 Combine like terms: 0.538144962 + 0.36 = 0.898144962 x = 0.898144962 Simplifying x = 0.898144962

Subproblem 2

x + -0.36 = -0.538144962 Simplifying x + -0.36 = -0.538144962 Reorder the terms: -0.36 + x = -0.538144962 Solving -0.36 + x = -0.538144962 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.36' to each side of the equation. -0.36 + 0.36 + x = -0.538144962 + 0.36 Combine like terms: -0.36 + 0.36 = 0.00 0.00 + x = -0.538144962 + 0.36 x = -0.538144962 + 0.36 Combine like terms: -0.538144962 + 0.36 = -0.178144962 x = -0.178144962 Simplifying x = -0.178144962

Solution

The solution to the problem is based on the solutions from the subproblems. x = {0.898144962, -0.178144962}

See similar equations:

| 3k-20=4 | | 2(x+8)-4(x-1)=6 | | x+2/5=3 | | 3x^2=100 | | 7/4w=28 | | 3y+5=2y+8 | | 2y^2+5y-3y=0 | | 6-4y=0 | | 6x+12=2x+6 | | 4y^2+y=0 | | 3x+9x+10=33-9 | | 3s-17=53+7s | | 3y-8=32+9y | | x+3x+3x-5=55 | | 4(x+8)-12=80 | | -4a-10b=-7 | | 421*35= | | 4x-6x=3x+10 | | 12*13= | | 5x+52=11x+12 | | x+x=320 | | (-x+4)(x-3)=-1 | | (x+4)(x-3)=-1 | | 7x-2=-44 | | 4x^2+2x+k=0 | | -19+12=-14m-8 | | 4x-25=2x+8 | | -8n-4-=-2+n-6-8n | | 9y+7= | | 2+6Y=12 | | 2p^2+7/2=8p | | 5x=11-2y |

Equations solver categories